Deciphering the Role of Innate Lymphoid Cells Group 3 in the Gut Microenvironment: A Narrative Review of Their Novel Contributions to Autoimmune Disease Pathogenesis - Wang H; Wang T; He Z; Wen C; Huang L; Wang M (Journal of Inflammation Research)
Hongli Wang,1,2 Tengyue Wang,1,2 Zhixing He,1,2 Chengping Wen,1,2 Lin Huang,1,2 Mingzhu Wang1,2 1Research Institute of Chinese Medical Clinical Foundation and Immunology, School of Basic Medical Science, Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China; 2Key Laboratory of Chinese Medicine Rheumatology of Zhejiang Province, Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of ChinaCorrespondence: Lin Huang; Mingzhu Wang, Email huanglin@zcmu.edu.cn; 17826866741@163.comAbstract: Type 3 Innate lymphoid cells (ILC3s) play a crucial role in intestinal immune function by serving as an innate effector that contributes to early-life defense against pathogens and helps protect the intestines from bacterial infections. ILC3s exert their immune function through cytokine secretion, patrolling actions and the generation of memory ILC3s that aid in repairing epithelial tissue and preserving mucosal barrier integrity. Moreover, dysregulation of ILC3s function has been implicated in the pathogenesis and progression of autoimmune diseases. This comprehensive review aims to explore the interactions between gut microbes, gut microbial metabolites, and diet in relation to ILC3s within the context of the gut microenvironment. Furthermore, the gut microenvironment has the potential to influence distant extra-intestinal sites through immunomodulation, thereby modifying their risk of inflammation. The gut has emerged as a significant focus of autoimmune disease research in recent years. However, the relationship between gut ILC3s and autoimmune diseases remains poorly understood. This paper aims to examine the potential association between ILC3s and autoimmune diseases.Keywords: ILC3s, IL-22, short-chain fatty acids, rheumatoid arthritis, systemic lupus erythematosus, ankylosing spondylitis